TECHNOLOGY OF WASTE PROCESSING OF THE CLOTHING INDUSTRY INTO CONSUMABLE MATERIALS FOR 3D PRINTING - POLISHCHUK, ANDRII; POLISHCHUK, OLEH; LISEVICH, SVITLANA; HORIASHCHENKO, SERHIY; URBANIUK, YEVHEN (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article describes the prospects of using polymer waste from the clothing industry for the manufacture of finished products by 3D printing. General information about waste generated in the process of manufacturing finished products, in particular about polyester and nylon, is provided. These materials are used in various industries for the manufacture of finished products. Their varieties are considered and their characteristics, advantages and disadvantages are described. The existing methods of processing waste polymer materials, as well as the stages of production of polymer granules from them, are given. It is noted that mechanical recycling of polymers is one of the most promising methods of processing waste polymer materials. The technology of processing polymer waste into finished products by the 3D printing method is proposed, which reduces the number of operations for obtaining a finished product compared to the existing ones. For the purpose of further experimental research, polyester and nylon textile materials were selected for further processing. The importance of developing effective devices for shredding garment industry waste and its design methods is noted. Grinding of polymer waste from the clothing industry was carried out using an experimental installation that allows taking into account all factors that have an impact on this process. Samples of crushed polymer materials are given. Selection of equipment for extruding crushed polymers has been carried out. The design of the screw of the extrusion machine for feeding crushed polymer in the form of fibers or small pieces of textile material was developed and manufactured. Experimental studies on the production of filament for 3D printing from crushed polymers have been conducted. The optimal modes of performing this technological operation on the specified equipment are determined. It has been experimentally confirmed the possibility of re-processing crushed polymer material waste into finished products using 3D printers that use granules or crushed polymer waste as raw materials.
Keywords: polymer; recycling; polyester; extrusion; extruder; 3D printing; 3D printer